Tinjauan Air Minum Kemasan Dalam Prespektif Tingkat Kepuasan Pelanggan - Irwan Wunarlan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Today, caution toward customers satisfication and dissatisfication is bigger and bigger. The competation is very stick with a great number of produsen in the same field. Therefore, each company must orientation to customers satisfication as particular goals. Desire and wish customers is not easy desribe. The customers always is not tell about wish them and there are many products is not success because misunderstanding wish customer. The drinking water package company must orientation to its customer need. In several years ago, Total Quality Management (TQM) is philosophy paradigm which is looking by industri and academic. Traditional Approach, Description Analysis and Structure Approach with Contigency Table and Chi-Square are technique for measuring customers satisfication as quality function in support TQM applied. This research will discuss about how to know level of customers satisfication toward quality drinking water package to increase quality product. Based on questionnaire given to the drinking water of package customers in research area then data collected and done data tabulation. According to data tabulation later then data analysed. It can be inffered that : (1) Result of Chi-square consist of Chi-table are 9.4877285, probability value are 0.1183145 and Chi-Count are 7.3541483. Showed that Chi-count (7.3541483) < Chi-table (9.4877285) and based on result computer calculation, P-valuae are 0.1183145 is greater than level of significant (0.05). It mean contigency table is independent or customers satisfication towards product of drinking water of package is not dependent of customers gander, (2) customers preception towards indicator of quality product of drinking water of package is the best than same product from competitor. It described in avarage of quality indicators value are 3.722. If this value, we will comparative with standard value, so avarage of quality indicator value are 3.693 is positive category, (3) avarage of relative index value give very satisfication to variables customer are (a) the product is delicious, (b) high brand reputation, and the variables customers have lower are (a) brand is containt product information, (b) product is suitable for all customers and (c) competitive price.